2004
DOI: 10.1016/j.bbamcr.2004.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of extracellular-signal regulated kinase is required for phagocytosis by Lymnaea stagnalis haemocytes

Abstract: Haemocytes are the primary defence cells of molluscs. In the present study, extracellular-signal regulated kinase (ERK) 1/2-like proteins were identified within Lymnaea stagnalis haemocytes, with apparent molecular weights of 44 and 43 kDa, respectively. Mitogen-activated protein kinase (MAPK) activity assays have confirmed that the L. stagnalis ERK possesses kinase activity towards Elk-1. Challenge of haemocytes with bacterial lipopolysaccharide (LPS) resulted in a transient activation of ERK, and immunocytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…Because signalling pathways are known to regulate haemocyte defence responses such as phagocytosis and H 2 O 2 output [7], [9][12], and because these defence responses were supressed in R. lagotis haemocytes as a result of T. regenti infection, we aimed to determine PKC and ERK activation in haemocyte monolayers derived from uninfected and infected R. lagotis . Western blotting of haemocyte proteins with anti-phosphospecific PKC and ERK antibodies, which detect only the active forms of these kinases in snails [7], [8], [27], followed by densitometric analysis of immunoreactive bands from several independent blots revealed that PKC and ERK phosphorylation were reduced by 57% and 55%, respectively, in haemocytes from infected snails when compared to those from uninfected snails (p<0.01; Figure 7A–B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because signalling pathways are known to regulate haemocyte defence responses such as phagocytosis and H 2 O 2 output [7], [9][12], and because these defence responses were supressed in R. lagotis haemocytes as a result of T. regenti infection, we aimed to determine PKC and ERK activation in haemocyte monolayers derived from uninfected and infected R. lagotis . Western blotting of haemocyte proteins with anti-phosphospecific PKC and ERK antibodies, which detect only the active forms of these kinases in snails [7], [8], [27], followed by densitometric analysis of immunoreactive bands from several independent blots revealed that PKC and ERK phosphorylation were reduced by 57% and 55%, respectively, in haemocytes from infected snails when compared to those from uninfected snails (p<0.01; Figure 7A–B).…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting of haemocyte proteins with anti-phosphospecific PKC and ERK antibodies, which detect only the active forms of these kinases in snails [7], [8], [27], followed by densitometric analysis of immunoreactive bands from several independent blots revealed that PKC and ERK phosphorylation were reduced by 57% and 55%, respectively, in haemocytes from infected snails when compared to those from uninfected snails (p<0.01; Figure 7A–B). We reasoned, therefore that ERK expression might also be suppressed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations